Fabrication of IrO2 decorated vertical aligned self-doped TiO2 nanotube arrays for oxygen evolution in water electrolysis. (10th May 2018) - Shi, Yan; Lu, Zhuoxin; Guo, Lili; Wang, Zhida; Guo, Changqing; Tan, Hongyi; Yan, Changfeng
Abstract: To fabricate effective and stable OER electrode in water electrolysis, self-doped TiO2 nanotube arrays which has a higher electrical conductivity than pristine TiO2 nanotube arrays was used as the support for loading IrO2 . The self-doped TNTA was fabricated by a simple electrochemical reduction of TNTA in neutral electrolyte solution, and then IrO2 nano particles were deposited by pulse electro-deposition method. The cyclic voltammetric behavior, electrical conductivity and micro structure of self-doped TNTA prepared at different reduction potential were characterized to obtain an optimal performance, and self-doped TNTA prepared under −1.9 V (vs. Ag/AgCl) shows the best electrochemical performance. After depositing IrO2, the OER activity and stability of new electrodes were also determined. Due to the enhanced electrical conductivity of support, the mass activity of IrO2 /self-doped TNTA are 50 times higher than IrO2 /TNTA. The OER stability of new electrode was evaluated under constant current of 5 mA/cm 2, IrO2 /TNTA and IrO2 /Ti were also tested for comparison. A higher stability of IrO2 /self-doped TNTA electrode is observed than the other two electrodes, and XPS studies indicate a lower oxidation state of Ir in IrO2 /self-doped TNTA, this shows a possible interactions between IrO2 and the new support. Highlights: The mass activity of Iridium in IrO2 /self-doped TNTA are 50 times higher than IrO2 /TNTA. The IrO2 /self-doped TNTA electrode exhibits a higher OER stability than IrO2 /TNTA and IrO2 /Ti electrode. The oxidation state of Ir in IrO2 /self-doped TNTA is lower than IrO2 /TNTA.